2004
DOI: 10.1023/b:card.0000029031.87129.05
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Exercise on Plasma Concentrations of Nebivolol, Bisoprolol and Carvedilol

Abstract: Plasma concentrations of bisoprolol increased during exercise and returned to baseline during recovery, a behaviour which would have been predicted according to present knowledge. However, exercise had no effect on plasma concentrations of nebivolol and carvedilol, a finding that is in contrast to previous results with other beta-blockers such as propranolol and atenolol. We conclude that both nebivolol and carvedilol are not taken up into and released from adrenergic nerves during exercise, a feature that cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…In addition to the different effects of beta-blockers obtained in the present study, it was shown recently that pharmacokinetic properties of third generation beta-blockers also differ significantly from those of first and second generation beta-blockers: It was shown previously that plasma concentrations of propranolol, atenolol and bisoprolol markedly increase during exercise [25,26,27,28,29]. The reason for this increase might be the fact that propranolol and atenolol are taken up into, stored in and released from adrenergic cells during exercise together with epinephrine and norepinephrine, thus causing an increase of plasma concentrations of these drugs together with those of epinephrine and norepinephrine during exercise [30,31,32,33,34,35].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition to the different effects of beta-blockers obtained in the present study, it was shown recently that pharmacokinetic properties of third generation beta-blockers also differ significantly from those of first and second generation beta-blockers: It was shown previously that plasma concentrations of propranolol, atenolol and bisoprolol markedly increase during exercise [25,26,27,28,29]. The reason for this increase might be the fact that propranolol and atenolol are taken up into, stored in and released from adrenergic cells during exercise together with epinephrine and norepinephrine, thus causing an increase of plasma concentrations of these drugs together with those of epinephrine and norepinephrine during exercise [30,31,32,33,34,35].…”
Section: Discussionmentioning
confidence: 52%
“…The reason for this increase might be the fact that propranolol and atenolol are taken up into, stored in and released from adrenergic cells during exercise together with epinephrine and norepinephrine, thus causing an increase of plasma concentrations of these drugs together with those of epinephrine and norepinephrine during exercise [30,31,32,33,34,35]. However, it was shown recently that plasma concentrations of carvedilol [36, 37] and nebivolol [29] do not increase during exercise, thus being a further major difference between third generation beta-blockers and those of the first and second generation [38]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most other BAAs, nebivolol is not taken up into, stored in and released from adrenergic cells during exercise together with epinephrine and norepinephrine. Exercise had no effect on plasma concentrations of nebivolol (rest: 0.273 ± 0.029 ng/mL, exercise: 0.274 ± 0.035 ng/mL, recovery: 0.272 ± 0.035 ng/mL) . This might explain why other BAAs are still effective after withdrawal even when they are no longer detectable in plasma.…”
Section: Methodsmentioning
confidence: 94%
“…Also similar to nebivolol, plasma concentrations of carvedilol do not increase during exercise [8], thus indicating that carvedilol is not concomitantly released with adrenaline and noradrenaline from adrenergic cells during exercise [12,13], another finding unique to carvedilol and nebivolol among all ß-blockers so far investigated.…”
Section: Carvedilolmentioning
confidence: 85%
“…However, plasma concentrations of nebivolol do not increase during exercise [8], thus indicating that nebivolol is not concomitantly released from adrenergic cells during exercise with adrenaline and noradrenaline. 25 mg carvedilol (Carved) racemate and 5 mg nebivolol (Nebiv) racemate on nocturnal excretion of 6-sulfatoxy-melatonin (a6MTS, the main metabolite of melatonin that is almost completely released in urine): The ß-blocking (S)-enatiomers of propranolol and atenolol decreased aMT6s by more than 80%, whereas the non-ß-blocking (R)-enantiomers of propranolol and atenolol as well as the racemic mixtures of carvedilol and nebivolol had no effect.…”
Section: Nebivololmentioning
confidence: 86%